If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5v + 17 = 3v + 17 Reorder the terms: 17 + -5v = 3v + 17 Reorder the terms: 17 + -5v = 17 + 3v Add '-17' to each side of the equation. 17 + -17 + -5v = 17 + -17 + 3v Combine like terms: 17 + -17 = 0 0 + -5v = 17 + -17 + 3v -5v = 17 + -17 + 3v Combine like terms: 17 + -17 = 0 -5v = 0 + 3v -5v = 3v Solving -5v = 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. -5v + -3v = 3v + -3v Combine like terms: -5v + -3v = -8v -8v = 3v + -3v Combine like terms: 3v + -3v = 0 -8v = 0 Divide each side by '-8'. v = 0 Simplifying v = 0
| y=.80(101-100)+100 | | y=-2(-2)+5 | | 7x+10+3(4-9x)=18 | | y=.80*101+100 | | 6x-15=2x+19 | | 125=-.5x^2+25x-100 | | ln(2x)=ln(x+1) | | 17x^2-13x=0 | | 2-2(2x-2)=-(3x+3) | | -12x-32=4x+16 | | x^4-7x^2-144=0 | | 2n+3+4n=5+6n-2 | | -(z+9)+(6z+1)=-6(z+1) | | 5x-13=7x-(4x-27) | | -16x^2+60x+6=0 | | -(z+4)+(4z+1)=-2(z+1) | | Y=X^2-10x+5 | | a+9=13 | | (4x+2x)+(x+6x)= | | -2(r-1/2)=-2 | | 5(6z-1)-3(z+3)=10(z+1) | | 12z-8=4z-24 | | -5y-21=2y | | y=-3+4 | | 1+2g=7 | | X^2-12=-X | | 7=9f(223) | | -5-[(9-7)-(-10-7)]=X | | (8m-4m+5)+(7m-4m+12)= | | 4x-2=2x-4 | | -6x=3c^2+4 | | (11110)2= |